Investigation on differentiation behaviors of multiple hydrocarbon components in intra-source migration within matrix-type shale oil reservoirs - Yaohua Li; Fuqiang Xu; Xingyou Xu; Caiqin Bi; Yu Shi; Rubing Han (Fuel, 2027)

Rethinking spent mushroom substrate: from lignocellulosic waste to soil–microbiome bioresource for circular agriculture - Rizwan Khan; Jianou Gao; Yousif Abdelrahman Yousif Abdellah; Dong Liu; Fuqiang Yu (Bioresource Technology, 2026)

Characterizing the changes and regional drivers of tropical cyclone intensification over the western North Pacific - Yuanke Wu; Tao Gao; Xi Xiao; Wei Zhang; Fuqiang Cao; Yang Yu; Yuzhi Liu; Yumin Zhang (Global and Planetary Change, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Selective electrocatalytic hydrogenation of phenol to value-added products using PtRu electrodes: closing carbon balance by capturing gas-phase cyclohexane - Xiaolong Lu; Hongjie Guo; Yu Li; Fuqiang Liu; Qizheng Zhuo; Shuai Yang; Xiaohong Guan; Changyong Zhang (ENGINEERING Environment, 2026)

Correlation-based insights into nicotine detoxification and humification during tobacco waste co-composting: Optimization of amendment ratio and microbial functional mechanisms - Shimei Yang; Yousif Abdelrahman Yousif Abdellah; Dong Liu; Zhanping Huang; Qiang Gao; Fangneng Lou; Dou Tingting; Zhuyue Yan; Rizwan Khan; Jianwei Liu; Ziyan Zhou; Elsiddig A.E. Elsheikh; et al. (Journal of Environmental Chemical Engineering, 2026)

Boride-derived catalysts for hydrogen evolution: Precursor-controlled reconstruction toward M-Co(OH)2 and M-Ni(OH)2 active phases and their application in Al-H2O batteries - Chen Chen; Zhenyu Wang; Yasen Li; Jiayao Gao; Xin Chen; Mingjie Jia; Die Shao; Yiming Wang; Xuejian Li; Fuqiang Yu; Guangwen Xu; Junli Xu; et al. (Journal of Environmental Chemical Engineering, 2026)

Semantic Segmentation and Application of Fractures and Vugs in Electrical Imaging Logs Based on MFAP-Transformer - Yu Zeng; Fuqiang Lai; Zhihui He; Haitao Wang; Zhaohui Huang; Shaolong Zhang; Ya Yang (Applied Geophysics, 2026)

Waste-to-resource bioremediation: Synergistic immobilization of multi-metal contamination by Ageratina adenophora-derived compost-biochar with microbial inoculants restores soil microbial genetic potential - Yousif Abdelrahman Yousif Abdellah; Jianou Gao; Tian Ma; Rizwan Khan; Shimei Yang; Zhenyan Yang; Muhammad Shoaib Rana; Abdelsalam Mohammed Daoud Yahya; Yanliang Wang; Jianwei Liu; Zhuyue Yan; Jing Yuan; et al. (Chemical Engineering Journal, 2026)

A Non-spinal Neural Circuit for Transmitting Information of Bladder Conditions - Zhenxiang Zhu; Zhuang Liu; Zan Wang; Guangfu Cui; Mei-Yu Shi; Kunzhang Lin; Yuxiang Qiu; Tengxiao Si; Peng Chen; Qing Liu; Guo-Qiang Bi; Jie Wang; et al. (Neuroscience Bulletin, 2026)

Beyond magnetic-field enhanced peroxymonosulfate activation: Interfacial restructuring of nanoscale Fe0 for efficient contaminant degradation - Jingyang Luo; Ran Yu; Xinyi Liu; Chao He; Fuqiang Liu; Jianglei Xiong; Shilong Jiang; Song Cheng; Yiping Li (Chemical Engineering Journal, 2026)

Stick–Slip Friction and Surface Contact Density of Bare Granite Joint Affected by Cyclic Normal Stress - Kang Tao; Heinz Konietzky; Fuqiang Gao; Rui Wu; Wengang Dang; Chenghao Li; Yu Liu (Rock Mechanics and Rock Engineering, 2026)

Integrating elite selection and micropropagation: a production line for early-stage domestication of Vaccinium bracteatum - Chuizheng Xia; Muhammad Junaid Rao; Ying Wu; Yuanyuan Li; Xuefeng Wang; Weicong Hong; Mengxue Wang; Yihong Jin; Jiani Zhu; Xuan Yu; Haidi Yuan; Jiao Wang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Root carboxylate release of native plants in the Hengduan Mountains: Insights from X-ray fluorescence results on leaf manganese concentrations in herbarium specimens - Guixian Zheng; Yanliang Wang; Erman Xie; Jing Yuan; Jian Zhan; Meng Yang; Xuewei Hu; Xuedan Xie; Fuqiang Yu; Hans Lambers (Soil Ecology Letters, 2026)

Fungal Pathogens in Morel Cultivation: Impact, Management Strategies, and Future Directions - Entaj Tarafder; Meimei Wang; Mir Muhammad Nizamani; Saowaluck Tibpromma; Joturong Kumla; Diptosh Das; Ang Rinzing Sherpa; Yong Wang; Fuqiang Yu; Nakarin Suwannarach; T. D. C. Priyadarshani; M. V. S. S. Mudugama; et al. (New Zealand Journal of Botany, 2026)
Fungal pathogens pose a serious threat to the cultivation of morels ( Morchella spp.), impacting both yield and quality and, consequently, the economic viability of morel farming. This review explores the diverse range of fungal pathogens affecting morels, including Albomorchellophila morchellae , Cladobotryum protrusum , Clonostachys aureofulvella , Clonostachys rosea , Cylindrodendrum alicantinum , Diploöspora longispora , Fusarium equiseti , Lecanicillium aphanocladii , Luteonectria nematophila , Pseudodiploöspora longispora , Purpureocillium lilacinum , and Trichothecium roseum , elucidating their life cycles and the damage they cause. The review also highlights existing management strategies, encompassing cultural practices, biological control, chemical control, and the cultivation of resistant varieties. Furthermore, it explores recent advancements in mycology, plant pathology, and biotechnology that offer promising avenues for improved disease management. These include improved diagnostics, precision agriculture, predictive modeling, genome editing, natural biocontrol agents, and organic fungicides. The review concludes with insights into future research directions aimed at combining and refining these strategies to ensure sustainable, profitable morel cultivation. While challenges such as technical requirements, ethical considerations, and acceptance by farmers and consumers remain, the potential benefits to the industry and global food security make this a pressing and rewarding field of study.

Biochar-Piriformospora indica interaction alters rhizospheric bacterial communities and enhances root metabolite secretion of maize cultivated in albic soils - Yu Zhang; Bo Zhang; Hongjiu Yu; Jie Liu; Kun Li; Qiuju Wang; Fuqiang Song (Plant and Soil, 2026)

Dual-phase bioconversion transforms toxic invasive Ageratina adenophora into nutrient-rich fertilizer: Synergistic detoxification by composting and black soldier fly larvae - Yousif Abdelrahman Yousif Abdellah; Xiaofei Shi; Dou Tingting; Jianou Gao; Shimei Yang; Fengming Zhang; Zhenyan Yang; Chengmo Yang; Elsiddig A.E. Elsheikh; Zhuyue Yan; Rizwan Khan; Rashid Mohamed Ahmed; et al. (Chemical Engineering Journal, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

Compartment-specific assembly and functional characterization of the bacterial microbiome in a Pinus radiata- Lactarius deliciosus plantation system - Jing Yuan; Yanliang Wang; Xueqiong Zhang; Zhuyue Yan; Ran Wang; Chengmo Yang; Xinhua He; Jesús Pérez-Moreno; Fuqiang Yu; Yi Zheng (Applied Soil Ecology, 2026)

Oxalotrophic bacteria in the ectomycorrhizosphere play an essential role in phosphorus mobilization - Jing Yuan; Zhuyue Yan; Yuanhao Wang; Shaolin Fan; Jiaxu Chen; Kejiang Ye; Guixian Zheng; Shanping Wan; Yi Zheng; Fuqiang Yu; Yanliang Wang; Hans Lambers; et al. (Soil Biology and Biochemistry, 2026)

Cholesterol-Based Lipid Nanoparticles as an Intracellular Drug Reservoir for Enhanced Tumor Therapy - Qi Jiang; Yihe Qiu; Peirong Li; Caini Yu; Tingting Meng; Fuqiang Hu; Cheng Wang; Hong Yuan (Pharmaceutical Research, 2026)

Evaluation and prediction of the coupling coordination of the “water-economy-ecology” system in the central plains urban agglomeration - Jiageng Hu; Peifang Wang; Fuqiang Wang; Peiheng Liu; Subing Lü; Cheng Lü; Furong Yu (Environment, Development and Sustainability, 2026)

Inhibitory activity and antifungal mechanism of venturicidin A against Pyricularia oryzae - Yinan Wang; Lin Qi; Fei Liu; Chentong Yan; Fuqiang Zhao; Zhiguo Yu (Pesticide Biochemistry and Physiology, 2026)

Spatiotemporal trajectory of senescence in mesocarp cell clusters of Hylocereus undatus based on single-cell and spatial transcriptomics - Yajing Tian; Xiang Ji; Mingyue Lv; Lili Lu; Tengfei Yu; Jingya Wang; Jingyu Xu; Guanzhi Wang; Fuqiang Li; Yiyang Song; Yang Li; Xinyue Pang; et al. (Journal of Plant Physiology, 2026)

A novel accident causation analysis model of hazardous chemical production accidents based on 2–4Model and Bayesian Network - Yidu Hong; Yu Zhang; Xiongfei Pei; Ningning Yang; Geng Peng; Fuqiang Yang; Meijuan Lan (Process Safety and Environmental Protection, 2026)

Performance stability and recovery strategy of pre-denitrification coupled partial nitritation/anammox-hydroxyapatite processes for enhanced organic matter, nitrogen and phosphorus removal from swine manure digestate - Yunzhi Qian; Shilong He; Fuqiang Chen; Junhao Shen; Chao Rong; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2026)

Shifts in epidemic patterns and age dynamics of RSV, IFV, and SARS-CoV-2 in Chinese children following COVID-19 non-pharmaceutical intervention relaxation, 2017 − 2024 - Yiguo Zhou; Jian-Bo Xia; Meimei Luo; Wan-Xue Zhang; Shan-Shan Zhang; Le Ao; Han Yang; Qin-Yi Ma; Juan Du; Yu-Ting Wang; Ninghua Huang; Xing-Wen Hu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Phytochemical-driven detoxification: Impact of Ageratina adenophora application on heavy metal bioavailability, pathogens, and antibiotic resistance genes removal in composting systems - Yousif Abdelrahman Yousif Abdellah; Dou Tingting; Jianou Gao; Shimei Yang; Zhenyan Yang; Chengmo Yang; Ayodeji Bello; Elsiddig A.E. Elsheikh; Dong Liu; Fuqiang Yu (Journal of Hazardous Materials, 2025)

Direct Z-scheme Sc2CF2/SnS2 heterojunction with high solar-to-hydrogen efficiency for photocatalytic water splitting - Fuqiang Ai; Qingquan Xiao; Jianfeng Ye; Dahai Yu; Songguo Yu; Liqin Zhang; Quan Xie; Sheng Li; Xiaoping Wu (Journal of Environmental Chemical Engineering, 2025)

Discovering novel type I collagen fragments from Cyprinus carpio supporting bone regeneration - Jianhua Zeng; Miao Chen; Xinglong Wang; Huan Yu; Liang Zhang; Yongxing Peng; Ping Wan; Zhongshi Huang; Fuqiang Ma; Jingtang Li (Functional & Integrative Genomics, 2025)

Composting Ageratina adenophora with spent mushroom substrate: Phytochemical degradation, greenhouse gas mitigation, and enhanced nutrient cycling - Yousif Abdelrahman Yousif Abdellah; Dong Liu; Dou Tingting; Jianou Gao; Shimei Yang; Zhenyan Yang; Chengmo Yang; Elsiddig A.E. Elsheikh; Shanshan Sun; Ayodeji Bello; Fuqiang Yu (Journal of Environmental Chemical Engineering, 2025)

Electronic properties and photocatalytic characteristics of promising S-scheme Hf2CO2/SnS2 heterojunction with high solar-to-hydrogen efficiency: First-principles calculations - Dahai Yu; Qingquan Xiao; Jianfeng Ye; Shengshang Lu; Songguo Yu; Fuqiang Ai (Journal of Environmental Chemical Engineering, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Impact of Ca supplement to the single-stage partial nitritation/anammox-hydroxyapatite process in treating swine manure digestate: deterioration mechanism and recovery strategy - Yunzhi Qian; Shilong He; Chao Rong; Yan Guo; Fuqiang Chen; Junhao Shen; Yu Qin; Yu-You Li (Chemical Engineering Journal, 2025)

Efficient and stable removal of organic matter, nitrogen and phosphorus from swine manure digestate by coupling high-rate activated sludge and single-stage partial nitritation/anammox-hydroxyapatite processes - Yunzhi Qian; Shilong He; Yan Guo; Fuqiang Chen; Junhao Shen; Yu Qin; Yu-You Li (Bioresource Technology, 2025)

Tobacco waste valorization through composting: A systematic review of biomass conversion efficiency and circular bioeconomy strategies - Yousif Abdelrahman Yousif Abdellah; Shimei Yang; Chengmo Yang; Zhenyan Yang; Elsiddig A.E. Elsheikh; Katharina Maria Keiblinger; Taha Ahmed Mohamed; Muhammad Shoaib Rana; Dong Liu; Fuqiang Yu (Biomass and Bioenergy, 2025)

Systematic understanding of titanium suboxides and their energy applications - Hongji Yu; Xuzhou Sun; Zhuoran Lv; Yuge Cao; Wujie Dong; Yuqiang Fang; Fuqiang Huang (Science Bulletin, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Determine leaf manganese concentration to estimate rhizosheath carboxylates of mycorrhizal plants in forest ecosystems - Yanliang Wang; Meng Yang; Fuqiang Yu (Plant and Soil, 2025)

BI1 Activates Autophagy and Mediates TDP43 to Regulate ALS Pathogenesis - Yu Wang; Yuxiang Wang; Hanlan Yin; Zixuan Xiao; Zhichao Ren; Xueting Ma; Jingtian Zhang; Xueqi Fu; Fuqiang Zhang; Linlin Zeng (Molecular Neurobiology, 2025)

Fungal necromass contribution to carbon sequestration in global croplands: A meta-analysis of driving factors and conservation practices - Dong Liu; Ziyan Zhou; Shahid Iqbal; Ting Ting Dou; Gregory Bonito; Wei Liu; Shaoshan An; Caspar C.C. Chater; Jesus Perez-Moreno; Rongxiao Che; Davey L. Jones; Fuqiang Yu (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

Investigation of mooring breakage impact on dynamic responses of a 15 MW floating offshore wind turbine - Debang Nie; Yang Yang; Shuai Li; Jie Yu; Musa Bashir; Jiaqing Yin; Yajun Ren; Jungang Hao; Fuqiang Wang; Qianni Liu; Chun Li (Ocean Engineering, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Design, synthesis and biological evaluation of novel pyrimidine-phenylsulfonylfuroxan hybrids - Dongling Gu; Shihao Wang; Zichen Yang; Hongjing Chen; Jiahui Han; Lingling Chi; Fuqiang Yu; Hao Wang; Jiaxin Zheng; Peirong Zhao; Hongmin Liu; Yu Ke; et al. (Medicinal Chemistry Research, 2024)

Self-standing COF-MOF composite sandwich membranes with high permeability for dye separation - Bingbing Chen; Xing Gao; Xiaojiao Hou; Yuanlin Fu; Yuhang Li; Fuqiang Fan; Tieqiang Wang; Fanbao Meng; Yu Fu; Junchao Ma (Desalination, 2024)

Synergistic effects of biochar and laccase on nitrogen conversation and degradations of two artificial sweeteners during the sewage sludge composting - Jishao Jiang; Huilin Cui; Zhuyu Tang; Shipeng Wang; Ke Cheng; Chunyan Zhang; Tonghuan Yu; Jinghua Lv; Fuqiang Yu; Dong Liu (Chemical Engineering Journal, 2024)

Virome and metagenomic sequencing reveal the impact of microbial inoculants on suppressions of antibiotic resistome and viruses during co-composting - Ziyan Zhou; Katharina Maria Keiblinger; Yimei Huang; Parag Bhople; Xiaofei Shi; Shimei Yang; Fuqiang Yu; Dong Liu (Journal of Hazardous Materials, 2024)

Electrically driven enhancement on selective adsorption of nitrate by microporous carbon from wastewater: Synergism of functional groups and micropores - Yu Ge; Yue Wang; Yanqi Chen; Xinbing Xu; Zifan Liu; Zhonglong Yin; Yong Dai; Fuqiang Liu; Weiben Yang (Chemical Engineering Journal, 2024)

Removal of artificial sweeteners in wastewater treatment plants and their degradation during sewage sludge composting with micro- and nano-sized kaolin - Jishao Jiang; Rui Hou; Huilin Cui; Zhuyu Tang; Yousif Abdelrahman Yousif Abdellah; Caspar C.C. Chater; Ke Cheng; Fuqiang Yu; Dong Liu (Bioresource Technology, 2024)

N-acetyl-L-cysteine-modified macrophage membrane-coated VEGF sustained-release nanoparticles for treatment of myocardial infarction: A biomimetic nano-buffer for neutralization of detrimental factors and promotion of mature angiogenesis - Ke Zhu; Kun Wang; Yu Yao; Yinxia Zhu; Ziyang Zhu; Wenyuan Wang; Ruijie Qian; Zhiping Deng; Jun Zhao; Yunli Shen; Fuqiang Shao (Chemical Engineering Journal, 2024)

Optimizing hydraulic retention time of high-rate activated sludge designed for potential integration with partial nitritation/anammox in municipal wastewater treatment - Yanxiao Wei; Weizhe Xia; Min Ye; Fuqiang Chen; Yunzhi Qian; Yu-You Li (Bioresource Technology, 2024)

Correction to: Low FHL1 expression indicates a good prognosis and drug sensitivity in ovarian cancer - Xiaoying Chen; Yue Yu; Yuting Su; Lizhou Shi; Shanzhou Xie; Yi Hong; Xia Liu; Fuqiang Yin (Functional & Integrative Genomics, 2024)

Enhancing C and N turnover, functional bacteria abundance, and the efficiency of biowaste conversion using Streptomyces-Bacillus inoculation - Ziyan Zhou; Xiaofei Shi; Parag Bhople; Jishao Jiang; Caspar C.C. Chater; Shimei Yang; Jesus Perez-Moreno; Fuqiang Yu; Dong Liu (Journal of Environmental Management, 2024)

Purge strategy analysis of proton exchange membrane fuel cells based on experiments and comprehensive evaluation method - Tong Niu; Xingzi Yu; Caizhi Zhang; Gucheng Wang; Ming Han; Hongying Liu; Fuqiang Zhao; Qi Shuai (Fuel, 2024)

Multi-functional ion-pairing additive for efficient quasi-2D perovskite light-emitting diodes and solar cells - Xiangrui Du; Ying Li; Zhongkai Yu; Chang‐Mok Oh; Yuanyuan Zhang; Fengwu Liu; Eunhye Yang; Yoomi Ahn; Yongzan Chen; In‐Wook Hwang; Bo Ram Lee; Fuqiang Li; et al. (Chemical Engineering Journal, 2024)

Study on the combination effect of tunnel slope and longitudinal fire location on the asymmetric flow fields in a naturally ventilated tunnel - Longxing Yu; Xiwen Lei; Ping Huang; Chunxiang Liu; Hao Zhang; Fuqiang Yang (Tunnelling and Underground Space Technology, 2024)

Rapid start-up of an innovative pilot-scale staged PN/A continuous process for enhanced nitrogen removal from mature landfill leachate via robust NOB elimination and efficient biomass retention - Cancan Jiang; Liang Zhang; Yongzhi Chi; Shengjun Xu; Yawen Xie; Dongmin Yang; Yunzhi Qian; Fuqiang Chen; Weijun Zhang; Dongsheng Wang; Zhe Tian; Shujun Zhang; et al. (Water Research, 2024)

Experimental study on the mechanism of water on heat sink variation in catalytic partial steam reforming of supercritical n-decane - Fuqiang Chen; Yong Cao; Yu Feng; Zhenhua Wang; Deming Zhang; Jiang Qin; Xiaozhou He (Fuel, 2024)

Low FHL1 expression indicates a good prognosis and drug sensitivity in ovarian cancer - Xiaoying Chen; Yue Yu; Yuting Su; Lizhou Shi; Shanzhou Xie; Yi Hong; Xia Liu; Fuqiang Yin (Functional & Integrative Genomics, 2024)

Modeling rock damage during the long-term production process for hot dry rocks: Effects of additional conductivity on the production performance and economic efficiency - Fuqiang Xu; Yu Shi; Xianzhi Song; Guofeng Song; Shuang Li (Journal of Cleaner Production, 2024)

The magnitudes of multi-physics effects on geothermal reservoir characteristics during the production of enhanced geothermal system - Guofeng Song; Yu Shi; Fuqiang Xu; Xianzhi Song; Gensheng Li; Gaosheng Wang; Zehao Lv (Journal of Cleaner Production, 2024)

Improved performance of single-stage partial nitritation-anammox membrane bioreactor (PN/A MBR) by adding biofilm carriers: start-up, membrane operation and microbial structure - Fuqiang Chen; Hui Cheng; Yunzhi Qian; Junhao Shen; Wenzhao Zhao; Yu Qin; Yu-You Li (Chemical Engineering Journal, 2024)

The mechanism of ethanol blending on the variation of chemical heat sink in n-decane thermal cracking process - Yu Feng; Huihang Zhang; Deming Zhang; Fuqiang Chen; Xinhai Xu; Jiang Qin; Yi Jiao (Fuel, 2023)

Chitosan-based nano-micelles for potential anti-tumor immunotherapy: Synergistic effect of cGAS-STING signaling pathway activation and tumor antigen absorption - Shufen Zhang; Yingping Zeng; Kai Wang; Guangtao Song; Yiru Yu; Tingting Meng; Hong Yuan; Fuqiang Hu (Carbohydrate Polymers, 2023)

Simulated nitrogen deposition alters the ectomycorrhizal fungal community structure in northern Korean pine plantations - Gao Xiang; Ruotong Wu; Mengmeng Zhang; Kun Li; Xin He; Yu Song; Fuqiang Song (CATENA, 2023)

Review of high-temperature geothermal drilling and exploitation technologies - Xianzhi Song; Gensheng Li; Zhongwei Huang; Yu Shi; Gaosheng Wang; Guofeng Song; Fuqiang Xu (Gondwana Research, 2023)

Flame extension lengths beneath a double slope roof induced by gaseous fuel jet flame - Ping Huang; Shengtao Liu; Chunxiang Liu; Fuqiang Yang; Baihan Zhang; Longxing Yu (Fuel, 2023)

Coupled systems of pre-denitrification and partial nitritation/anammox improved functional microbial structure and nitrogen removal in treating swine manure digestate - Yunzhi Qian; Shilong He; Fuqiang Chen; Junhao Shen; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2023)

Design, synthesis and antitumor activity evaluation of 2,4,6-trisubstituted quinazoline derivatives containing piperidine moiety - Honglin Dai; Fuqiang Yu; Hao Wang; Lingling Chi; Chao Gao; Xiaojie Si; Yutong Zhang; Zhuo Qian; Peirong Zhao; Yingnan Zhu; Hongmin Liu; Qiurong Zhang (Medicinal Chemistry Research, 2023)

Design, synthesis and antitumor activity evaluation of 4,6,7-trisubstituted quinazoline derivatives containing benzothiazole moiety - Fuqiang Yu; Ying Xu; Hao Wang; Lingling Chi; Xiaojie Si; Chao Gao; Honglin Dai; Limin Liu; Zhengjie Wang; Yu Ke; Hongmin Liu; Qiurong Zhang (Medicinal Chemistry Research, 2023)

Design, synthesis and antitumor activity evaluation of tetrasubstituted pyrimidine derivatives containing methyl phenyl sulfone group - Chao Gao; Fuqiang Yu; Lingling Chi; Hao Wang; Honglin Dai; Xiaojie Si; Yuze Dong; Hongmin Liu; Qiurong Zhang (Medicinal Chemistry Research, 2023)

Design, synthesis and antitumor activity evaluation of 5-cyano-2,4,6-substituted pyrimidine derivatives containing acrylamide group - Fuqiang Yu; Lingling Chi; Hao Wang; Chao Gao; Honglin Dai; Limin Liu; Zhengjie Wang; Yu Ke; Hongmin Liu; Qiurong Zhang (Medicinal Chemistry Research, 2023)

Design, synthesis and antitumor activity evaluation of pyrimidine derivatives containing 4-hydroxypiperidine group - Lingling Chi; Hao Wang; Fuqiang Yu; Chao Gao; Honglin Dai; Limin Liu; Zhengjie Wang; Yuze Dong; Hongmin Liu; Qiurong Zhang (Medicinal Chemistry Research, 2023)

Heterogeneous Fe-Co dual-atom catalyst outdistances the homogeneous counterpart for peroxymonosulfate-assisted water decontamination: New surface collision oxidation path and diatomic synergy - Changqing Zhu; Fenxian Cun; Zhongwei Fan; Yu Nie; Qing Du; Fuqiang Liu; Weiben Yang; Aimin Li (Water Research, 2023)

Synthesis of a magnetic nanomaterial with core–shell structure for effective Au(III) recovery from solution with superior separation and one-step reduction - Xuefeng Yu; Chuanhao Yan; Jinglei He; Jinlong Zhang; Hangzhou lv; Fuqiang Liu; Jianlong Wang; Junfeng Liu; Xilong Wang (Chemical Engineering Journal, 2023)

Sponge-like, semi-interpenetrating self-sensory hydrogel for smart photothermal-responsive soft actuator with biomimetic self-diagnostic intelligence - Xingchen Cui; Zhezhi Liu; Bing Zhang; Xiaoduo Tang; Fuqiang Fan; Yu Fu; Junhu Zhang; Tieqiang Wang; Fanbao Meng (Chemical Engineering Journal, 2023)

The effect of microplastics on the depuration of hydrophobic organic contaminants in Daphnia magna: A quantitative model analysis - Wei Lin; Yu Li; Xiaoying Xiao; Fuqiang Fan; Jiakun Jiang; Ruifen Jiang; Yong Shen; Gangfeng Ouyang (Science of The Total Environment, 2023)

Long-term effects of phosphorus deficiency on one-stage partial nitrification-anammox system and recovery strategies - Liang Zhang; Zhe Tian; Yunzhi Qian; Fuqiang Chen; Yu-You Li; Xueke Wang; Cuilian Fu; Yongzhi Chi (Journal of Cleaner Production, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Effects of ozone addition and octane sensitivity on combustion characteristics of gasoline compression ignition engines - Zhongmiao Li; Jiaying Pan; Fuqiang Zhang; Yu He; Changwen Liu; Haiqiao Wei (Fuel, 2023)

Recent developments in anammox-based membrane bioreactors: A review - Fuqiang Chen; Yunzhi Qian; Hui Cheng; Junhao Shen; Yu Qin; Yu-You Li (Science of The Total Environment, 2023)

Increasing nitrogen and organic matter removal from swine manure digestate by including pre-denitrification and recirculation in single-stage partial nitritation/anammox - Yunzhi Qian; Junhao Shen; Fuqiang Chen; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2023)

The Characteristics and Laws of Fracture Damage in the Long-Term Production Process of High-Temperature Geothermal Resources - Fuqiang Xu; Yu Shi; Xianzhi Song; Gensheng Li; Zihao Song; Shuang Li (Rock Mechanics and Rock Engineering, 2023)

A Hydro-Economic Model for Optimizing Management of Mine Water: A Case Study in the Suancigou Coal Mine, Northwestern China - Wenping Mu; Xiong Wu; Hanghang Ding; Fuqiang Geng; Shuai Yu; Xiao Zhang (Mine Water and the Environment, 2022)

On capturing human agency and methodological interdisciplinarity in socio-hydrology research - David J. Yu; Melissa Haeffner; Hanseok Jeong; Saket Pande; Juliane Dame; Giuliano Di Baldassarre; Glenda Garcia-Santos; Leon Hermans; Rachata Muneepeerakul; Fernando Nardi; Matthew R. Sanderson; Fuqiang Tian; et al. (Hydrological Sciences Journal, 2022)

Bak interacts with AKT and is involved in TNFα/CHX-induced apoptosis - Jiayue Song; Fuqiang Zhang; Yu Wang; Yuxiang Wang; Jingtian Zhang; Zixuan Xiao; Xueqi Fu; Xuemin Xu; Linlin Zeng (Molecular and Cellular Biochemistry, 2022)

Plant growth-promoting activities of bacterial endophytes isolated from the medicinal plant Pairs polyphylla var. yunnanensis - Liu Tao; Liao Qiuhong; Yu Fuqiang; Zi Shuhui; Tian Suohui; Fan Linyuan (World Journal of Microbiology and Biotechnology, 2022)

Truffle species strongly shape their surrounding soil mycobiota in a Pinus armandii forest - Dong Liu; Mariana Herrera; Peng Zhang; Xinhua He; Jesús Perez-Moreno; Caspar C. C. Chater; Fuqiang Yu (Archives of Microbiology, 2021)

Mycorrhization of Quercus mongolica seedlings by Tuber melanosporum alters root carbon exudation and rhizosphere bacterial communities - Yanliang Wang; Ran Wang; Bin Lu; Alexis Guerin-Laguette; Xinhua He; Fuqiang Yu (Plant and Soil, 2021)

Response of Growing Season Gross Primary Production to El Niño in Different Phases of the Pacific Decadal Oscillation over Eastern China Based on Bayesian Model Averaging - Yueyue Li; Li Dan; Jing Peng; Junbang Wang; Fuqiang Yang; Dongdong Gao; Xiujing Yang; Qiang Yu (Advances in Atmospheric Sciences, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

An ultrahigh‐throughput screening platform based on flow cytometric droplet sorting for mining novel enzymes from metagenomic libraries - Fuqiang Ma; Tianjie Guo; Yifan Zhang; Xue Bai; Changlong Li; Zelin Lu; Xi Deng; Daixi Li; Katsuo Kurabayashi; Guang‐yu Yang (Environmental Microbiology, 2021)
Summary Uncultivable microbial communities provide enormous reservoirs of enzymes, but their experimental identification by functional metagenomics is challenging, mainly due to the difficulty of screening enormous metagenomic libraries. Here, we propose a reliable and convenient ultrahigh‐throughput screening platform based on flow cytometric droplet sorting (FCDS). The FCDS platform employs water‐in‐oil‐in‐water double emulsion droplets serving as single‐cell enzymatic micro‐reactors and a commercially available flow cytometer, and it can efficiently isolate novel biocatalysts from metagenomic libraries by processing single cells as many as 10 8 per day. We demonstrated the power of this platform by screening a metagenomic library constructed from domestic running water samples. The FCDS assay screened 30 million micro‐reactors in only 1 h, yielding a collection of esterase genes. Among these positive hits, Est WY was identified as a novel esterase with high catalytic efficiency and distinct evolutionary origin from other lipolytic enzymes. Our study manifests that the FCDS platform is a robust tool for functional metagenomics, with the potential to significantly improve the efficiency of exploring novel enzymes from nature.

Provenances originate morphological and microbiome variation of Tuber pseudobrumale in southwestern China despite strong genetic consistency - Dong Liu; Mariana Herrera; Fuqiang Yu; Jesús Pèrez-Moreno (Mycological Progress, 2020)

Land rehabilitation improves edaphic conditions and increases soil microbial biomass and abundance - Dong Liu; Baorong Wang; Parag Bhople; Fayzmamad Davlatbekov; Fuqiang Yu (Soil Ecology Letters, 2020)

Searching for an Optimized Single-objective Function Matching Multiple Objectives with Automatic Calibration of Hydrological Models - Fuqiang Tian; Hongchang Hu; Yu Sun; Hongyi Li; Hui Lu (Chinese Geographical Science, 2019)

Soluble Epoxide Hydrolase-Derived Linoleic Acid Oxylipins in Serum Are Associated with Periventricular White Matter Hyperintensities and Vascular Cognitive Impairment - Di Yu; Marie Hennebelle; Demetrios J. Sahlas; Joel Ramirez; Fuqiang Gao; Mario Masellis; Hugo Cogo-Moreira; Richard H. Swartz; Nathan Herrmann; Pak Cheung Chan; Jacqueline A. Pettersen; Donald T. Stuss; et al. (Translational Stroke Research, 2019)

Up-regulation of Siah1 by ethanol triggers apoptosis in neural crest cells through p38 MAPK-mediated activation of p53 signaling pathway - Fuqiang Yuan; Xiaopan Chen; Jie Liu; Wenke Feng; Xiaoyang Wu; Shao-yu Chen (Archives of Toxicology, 2017)